STUDI PERANCANGAN KAPAL PEMBERSIH GULMA AIR DENGAN SISTEM CONVEYOR DI KAWASAN OBYEK WISATA WADUK CENGKLIK DI KABUPATEN BOYOLALI - Sugeng Pardiana; Untung Budiarto; Kiryanto Kiryanto (Jurnal Teknik Perkapalan, 2013)
Cengklik Reservoir is one of the tourism in Boyolali, a reduced role for the growth of water hyacinth. The large number of water hyacinth cause sedimentation, decreased water quality, and heavy metal content contained in the sediment at the bottom of the reservoir. To mitigate the existing problems, sparked an idea of this study is to optimize the potential of the tourism area Cengklik Reservoir. This optimization process begins with cleaning regularly water hyacinth by using cleaning ship water weed with rotating conveyor system that instantly fit in the hatch ship. This is one of the breakthrough tool to reduce populations of water hyacinth (weeds) in Indonesia. This thesis discuss about ship design for optimal cleaning tourism area Cengklik Reservoir. This design will determine how the design of hydrostatic, resistance vessels, stability, and if the ship motion. The initial design of the cleaning vessel starts from the determination of the design parameters and constraints in accordance with vessel operations. The design of the boat using the method of comparison with the design using software Delftship, further process optimization to determine the optimal size of the main vessel. From the results of the calculation process, the main measure of optimal vessel obtained as follows: LOA = 13.30 m, LWL = 12.813 m, B = 4.00 m, H = 1.64 m, T = 0.90 m, engine power = 115 Hp, Vs = 8 knots.